(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Chronic obstructive pulmonary disease (COPD) is a leading global cause of disability and mortality, increasingly recognized as a systemic condition with multiorgan involvement. When complicated by arterial hypertension (AH), COPD patients face substantially elevated risk of renal dysfunction, yet this triad remains underinvestigated. Objective: To assess kidney dysfunction across COPD severity stages with and without comorbid AH, evaluate renal and vascular biomarkers, and investigate the efficacy of individualized therapy with Telsartan A (telmisartan + amlodipine) and eplerenone.Methods: 291 COPD+AH patients and 66 COPD-only controls were examined with pulmonary function tests, 24-hour blood pressure monitoring, and biomarker panels (cystatin-C, eGFR, aldosterone, E-selectin, type IV collagen, TNF-α, CRP).Results: COPD severity inversely correlated with eGFR and directly with all inflammatory and fibrotic markers; AH significantly worsened all renal parameters. Combined Telsartan A + eplerenone therapy improved FEV₁, eGFR, and reduced fibrotic/inflammatory markers. Conclusions: AH accelerates renal dysfunction in COPD. Early aldosterone, type IV collagen, and E-selectin measurement enables subclinical nephropathy detection. Telsartan A + eplerenone provides meaningful renoprotective benefit.